Formic Acid Pulping of Rice Straw - Suhardy, Daud; Siti Shuhadah, Md. Salleh; Mohd Nazry, Salleh; Farizul Hafiz, Kasim; Saiful Azhar, Saad (Universiti Malaysia Perlis (UniMAP), 2008)
Organized by Universiti Malaysia Perlis (UniMAP), 9th - 12th June 2007 at Park Royal Hotel, Penang.